Business Model Improvement: A Study Case of Financial Bookkeeping System and Marketing Strategy Creation - Nanda Inasovilizuari; Avanti Fontana (AIBPM Publisher, 2021)
The crisis that occurred in 2020 was caused by the COVID-19 pandemic. It changes the way humans live their life globally, which requires people to reduce mobility, thus making people in looking for new activities that can be done at home, one of which is gardening and planting. Amid external conditions that provide opportunities for incremental sales in-plant industry, ABC Orchid have not been able to take advantage of opportunities properly. This study case aims to solve the marketing and financial problems using the business development framework. The problem that arises is stagnated gross sales amid the booming in the plant industry. The substitution for income sources from large party consumers, such as hotels and offices become consumers from private markets, causing a stable gross basis compared to conditions before the pandemic. The methods used in this case study are in-depth interview with business owner and competitors from the same industry and self- administrative market survey. The results found that there are ineffective business activities in ABC Orchid, namely poor financial bookkeeping system and marketing activities that are not carried out consistently based on market. The phenomena of business ineffectiveness show the presence of a need-to-improve business model.